Analysis on the Implementation Plan to Increase the Joint Utilization Rate of National Research Facilities and Equipment - Jeon, Sehyeok; Hwang, Joo Sung; Kim, Miri; Kim, Seoyong (Proceedings - 2022 IEEE International Conference on Big Data and Smart Computing, BigComp 2022, 2022)
Science and technology, which has been rapidly developing in recent years, is attached to competitive investment and promotion policies between countries. As a result, various types of national R & D projects are being expanded and implemented, and investment and construction of research facilities and equipment have increased simultaneously. However, since the budget is limited, research and development results must be derived through the efficient operation and management of research facilities and equipment that have been invested and built. In this study, we are going to explore and derive policy suggestions for the realization of the improvement of the joint utilization rate for maximizing the utilization of research facilities and equipment, which is one of the main contents of Korea's national research facilities and equipment operation and utilization advancement plan. To this end, the flow is analyzed by using the ZEUS statistical data of the National Research Facility Equipment Promotion Center for the joint utilization rate of research facilities and equipment, and the necessity of enhancing policy acceptability was derived by focusing on the implementation plan of the 1st and 2nd advancement plans.
Keywords: Joint use of research facility equipment; National R & D project; Policy acceptability; Research and development; Research facilities; Research facility equipment; Research results; Science and Technology; Utilization rates; joint use of research facility equipment; National R & D project; policy acceptability; research facility equipment